Analisis Manajemen Komunikasi Kepala Sekolah Sebagai Leader untuk Meningkatkan Kinerja Guru di SD Muhammadiyah 22 Surakarta - Choirun Nisa; Aulia Kharisma; Rizka Silvia Fatmawati; Retno Fadillah (Departement of Mathematics Education, 2023)
Communication management is a strategic activity in educational institutions that is carried out primarily by school principals in channeling motivation to teachers and improving performance. This study explores and analyzes how the principal of SD Muhammadiyah 22 Sruni Surakarta implements communication management in increasing the quality of teacher work. Principal communication is one of the most important factors for directing better teacher performance. This research was conducted to measure how much influence school principal communication has on teacher performance. The method used in this research is a structured interview method used for primary data collection techniques. The implementation of this research is based on the low level of communication at SD Muhammadiyah 22 Surakarta, seen from the lack of communication that results in several aspects that can later hinder teacher performance, because the principal plays an important role in the school. The purpose of writing this article is to describe the communication behavior of school principals in managing and motivating teachers to improve their performance. The principal's communication with teachers can function to convey orders, distribute information or news, provide advice and provide an assessment of the performance of teachers.